If the maximum value of the expression x 2 y − y 2 x with 0 ≤ x ≤ 1 and 0 ≤ y ≤ 1 can be expressed as n m with m and n co-prime integer numbers find the value m + n
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
(x^2)y-x(y^2) = xy(x-y). This can be maxed by keeping at it uppermost level i.e. x= 1 This reduces the function to y(1-y) whose maximum value comes at y = 1/2 and the value of the function then is 1/4 = m/n Therefore, m+n = 5
Let A = x 2 y − y 2 x = x y ( x − y ) .
If x < y , then A < 0 .
If x > y , applying AM-GM inequality we have:
A = x y ( x − y ) ≤ 4 x ( y + x − y ) 2 = 4 x 3 ≤ 4 1
The equality holds if and only if x = 1 ; y = 2 1 .
So, the maximum value of A is 4 1 and m + n = 5 .
I was to hasty to look at the solutions, but I think I have one now. Assume WLOG that x > y such that x = y+a to give x 2 y − y 2 x = a y ( a + y ) ≤ 2 1 ( y 2 + a 2 ) ( y + a ) (by AM-GM) with equality when a = y such that x = 2y. Substituting this into our original inequality yields x 2 y − y 2 x = 2 y 3 = 2 ⇒ y = 1 , x = 2 1 ∴ x y ( x − y ) = 4 1
Problem Loading...
Note Loading...
Set Loading...
Using AM-GM: x 2 y − x y 2 = x y ( x − y ) ≤ ( 2 x y + x − y ) 2 = 4 ( ( x − 1 ) ( y + 1 ) + 1 ) 2
We then see that ( x − 1 ) ( y + 1 ) ≤ 0 for 0 ≤ x , y ≤ 1 .
So the max value occurs at 4 1 when x = 1 and y = 2 1